SPE Annual Technical Conference and Exhibition 1994
DOI: 10.2118/28550-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Study of Foam Diversion Processes for Matrix Acidization

Abstract: Factors key to the success of foam diversion processes for matrix acidization were measured in Berea cores. Foam mobility was low in high-permeability (847-md) Berea and higher in low-permeability (92 md) Berea, suggesting effective foam diversion. Injection of surfactant solution, emulating foam-compatible acid injected following foam, trapped some of the foam in place. but imputed diversion of acid was not as complete as diversion of foam itself. After a period of injection of liquid, more gas was displaced,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 30 publications
4
34
0
Order By: Relevance
“…As a result, pressure gradient increased in these experiments during liquid injection ( Fig. 2.8); all our previous experiments (Kibodeaux et al, 1994;Zeilinger et al, 1995;Rossen and Wang, 1999) had seen a decrease in pressure gradient during liquid injection.…”
Section: Initial Experiments: Water Saturation and Gas Trapping With supporting
confidence: 61%
See 1 more Smart Citation
“…As a result, pressure gradient increased in these experiments during liquid injection ( Fig. 2.8); all our previous experiments (Kibodeaux et al, 1994;Zeilinger et al, 1995;Rossen and Wang, 1999) had seen a decrease in pressure gradient during liquid injection.…”
Section: Initial Experiments: Water Saturation and Gas Trapping With supporting
confidence: 61%
“…The early modeling work of Kibodeaux et al (1994) concluded that the decline in pressure gradient seen shortly after liquid injection begins reduces the ability of foam to overcome the effects of permeability and divert the flow of liquid in acid-diversion processes.…”
Section: Initial Experiments: Water Saturation and Gas Trapping With mentioning
confidence: 99%
“…In the otherwise-successful SAG foam field trial in the Snorre field (Martinssen and Vassenden, 1999), low liquid injectivity caused fracturing of the injection well and loss of most of the injected surfactant in the second and third liquid slugs. Low liquid mobility after foam injection is also crucial to the success of foam-acid diversion processes (Kibodeaux et al, 1994).…”
Section: Task 2: Increase Sweep Efficiency With Foam Subtask 21: Mecmentioning
confidence: 99%
“…Previous experiments on liquid injection after foam had been conducted in conjunction with foam-acid diversion for well stimulation (Kibodeaux et al, 1994;Rossen and Wang, 1999). New experiments were conducted in parallel with a simulation study (Cheng et al, 2002).…”
Section: Task 2: Increase Sweep Efficiency With Foam Subtask 21: Mecmentioning
confidence: 99%
“…The insight gained into the FDL process is mainly due to co-workers [1994, 2001], who conducted systematic studies using two-stage experiments of foam placement followed by liquid injection. Rossen et al [1994Rossen et al [ , 2001 found that the pressure gradient declines in two steps. The pressure gradient first falls rapidly, but levels off to a value that remains relatively high.…”
Section: Introductionmentioning
confidence: 99%